COMPETITIVENESS: IS IT AN OBSESSION OR A NEED? - Seclen Luna, Jean Paúl (2009)
“Competitiveness is of growing interest in diverse groups: politicians try to improve it, lawmakers debate over it, editors publish on it, consultants make a living out of implanting it, and economists try to explain it and measure it.” This phrase is undoubtedly the basis to think about and to clarify the importance of competitiveness in daily life. It is clear that behind it lies a subtle but not less important need to understand this concept, because in one way or another we are all involved in these courses.